Оцінка геоекологічного стану озера Велике (Волинське Полісся) - Мартинюк, Віталій; Зубкович, Іван; Андрійчук, Сергій; Мартынюк, Виталий; Зубкович, Иван; Андрейчук, Сергей; Martyniuk, Vitalii; Zubkovych, Ivan; Andriichuk, Serhii (My University, 2018)
Актуалізуються питання геоекологічної оцінки озер Волинського Полісся у зв’язку з переходом України на басейновий принцип інтегрованого управління водними ресурсами. Обґрунтовуються результати геоекологічної оцінки (гідрологічна, гідрохімічна, геохімічна, ландшафтна) оз. Велике. Запропоновано використання бази даних із геоекологічної оцінки оз. Велике водогосподарськими, гідромеліоративними, природоохоронними відомствами, а також у збалансованому природокористуванні цілісної озерно-басейнової системи. The questions about geo-ecological assessment of the lakes of Volyn Polessia are being updated in connection with the transition of Ukraine to the basin principle of integrated water resources management. The results of geoecological estimation (hydrological, hydrochemical, geochemical, landscape) of Velyke Lake are grounded. The use of a database with a geo-ecological assessment of Velyke Lake by water management, hydro-ameliorative and environmental protection agencies as well as in a balanced environmental management of the whole lake-basin system has been suggested.
Оценка геоэкологического состояния озера Великое (Волынское Полесье)
The Assessment of the Geo-Ecological State of Velyke Lake (Volyn Polessia)
Keywords: озеро; озерно-басейнова система; донні відклади; геоекологічна оцінка озера; ландшафтна структура озера; lake; lake-basin system; bottom sediments; geo-ecological assessment of the lake; landscape structure of the lake